Graves disease in infancy: a patient presentation and literature review. (21st June 2021) - Alex-Ann Beliard, Kara; Shyamkumar, Srinidhi; Brar, Preneet Cheema; Rapaport, Robert
Abstract : Summary: We describe a case of an infant who presented with clinical features of hyperthyroidism. The child was found to be tachycardic, hypertensive and diaphoretic, she was noted to have poor weight gain and difficulty in sleeping. The child was admitted to the pediatric intensive care unit for care. She was found to have biochemical evidence of hyperthyroidism with positive thyroid stimulating immunoglobulin. She responded well to methimazole and propranolol and had a remarkable recovery. She is the youngest patient to be diagnosed with Graves disease in the English literature, at 12 months of life. Learning points: Hyperthyroidism must always be considered even at very young age, for patient presenting with poor weight gain and hyperdynamic state. Autoimmune diseases are becoming more common in infancy. Craniosynostosis and increased height for age are well-documented consequences of untreated hyperthyroidism in developing children.